Journal of Scheduling - Pinedo, Michael L.; Burke, Edmund K.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Scheduling provides a recognized global forum for the publication of all forms of scheduling research. First published in June 1998, Journal of Scheduling covers advances in scheduling research, such as the latest techniques, applications, theoretical issues and novel approaches to problems. The journal is of direct relevance to the areas of Computer Science, Discrete Mathematics, Operational Research, Engineering, Management, Artificial Intelligence, Construction, Distribution, Manufacturing, Transport, Aerospace and Retail and Service Industries. These disciplines face complex scheduling needs and all stand to gain from advances in scheduling technology and understanding. Unique - the only peer reviewed Journal with a broad coverage of the techniques and applications of scheduling across differing disciplines. Essential reading - an invaluable resource for all academics and practitioners involved in scheduling and scheduling-related problems. Officially cited as: J Sched.
Keywords: Business logistics; Operations research; Decision making; Mathematical optimization; Calculus of variations; Operations Research/Decision Theory; Calculus of Variations and Optimal Control; Optimization; Optimization; Artificial Intelligence; Supply Chain Management